Proceedings of the 2014 IEEE Emerging Technology and Factory Automation (ETFA) 2014
DOI: 10.1109/etfa.2014.7005031
|View full text |Cite
|
Sign up to set email alerts
|

Discrete event systems models and methods for different problems in healthcare management

Abstract: The rapidly growing of the world's population makes efficient Healthcare System (HS) management more and more important to all stakeholders, from patients and healthcare providers, to insurance companies and governments. The use of advanced information and networking technologies to advance health care management has long been recognized as the most effective way. Hence, healthcare organizations are often compared with manufacturing systems, and techniques and models from production systems are adapted to solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
(52 reference statements)
0
0
0
Order By: Relevance
“…DESS is an example of the most popular simulation technique due to its ability to model various variations and uncertainties within a system. Because of DESS's ability to intricately model complex systems, it is often used to address operational-level problems such as capacity planning, constraint identification, patient flow redesign, and other operational issues [20].…”
Section: Introductionmentioning
confidence: 99%
“…DESS is an example of the most popular simulation technique due to its ability to model various variations and uncertainties within a system. Because of DESS's ability to intricately model complex systems, it is often used to address operational-level problems such as capacity planning, constraint identification, patient flow redesign, and other operational issues [20].…”
Section: Introductionmentioning
confidence: 99%
“…Since the previous literature and evidence indicated that the monitoring and management of fall risk are complex and easily influenced by a plethora of factors (which could often lead typical fall risk screening tools to have a distorted view of the issue [10]), it has been hypothesized that investigating approaches that could allow a deeper overview of fall risk could aid in its limitation. To this aim, simulations have been proposed as an innovative solution in the healthcare field [11] due to the similarities that some healthcare systems present with other work environments [12]. In the context of simulation, discrete event systems (DES) have attracted much attention in the healthcare context due to, among other factors, the ability of this strategy to deal with complex problems, such as those encountered in healthcare settings [13].…”
Section: Introductionmentioning
confidence: 99%